Assembly of abundant and rare maize root-associated bacterial communities under film mulch - Li, Yüze; Hou, Quanming; Wang, Shengnan; Wen, Xiaoxia; Liao, Yuncheng (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2023)
In agroecosystem soils, abundant and rare biospheres have coexisted, resulting in complex interactive systems. It has remained unclear how agricultural practices have impacted the assembly of abundant and rare bacteria within root-associated compartments. The response of abundant and rare bacteria to plastic film mulch (PM) was investigated on a fine-compartment scale from bulk soil to rhizoplane, based on an in-situ experiment. The results indicated that root-associated communities were reactive to root selection, with abundant taxa having a greater niche breadth than rare taxa. The results of SourceTracker and the reduction of niche breadths from bulk soil to rhizoplane emphasized the role of roots in bacterial recruitment, with PM exerting greater host selection pressure. The assembly of abundant taxa was primarily impacted by variable selection, whereas that of rare taxa was influenced by homogeneous selection. PM amplified the impact of deterministic and stochastic processes on abundant and rare taxa. In contrast to rare taxa, abundant taxa were more frequently located in the center of networks, and PM greatly strengthened co-occurrence. Several abundant operational taxonomy units (OTUs) reflected their roles in maintaining microbial co-occurrence as keystone species. While the stochastic assembly of rare taxa was closely related to crop yield at the community level. Overall, these findings demonstrated how agricultural practices have had an impact on soil microbial communities along with the fine-scale compartments. They have demonstrated that PM would be having a major impact on the assembly of abundant and rare root-associated bacteria in drylands. [Display omitted] •Root-associated abundant and rare taxa within fine-scale compartments were studied.•Distinct abundant and rare subcommunities were shaped by plastic film mulch (PM).•PM altered the recruitment and assembly process of abundant and rare subcommunities.•Root traits play a vital role in the assembly of abundant and rare subcommunities.•Rhizoplane under PM enriched abundant taxa with plant growth-promoting ability.